ANALISIS SASTRA NARASI DALAM 1 RAJA-RAJA 17:7-16 BERDASARKAN METODE RICHARD PRATT MENGENAI RESPONS YANG MENGUBAH KRISIS MENJADI BERKAT - Aska Pattinaja; Marjani (Sekolah Tinggi Teologi Excelsius, 2024)
Widow Zarephat faced the toughest struggle to make a choice in her life, namely facing the threat of starvation with little flour and oil left and eventually dying or believing Elijah's words, that God could preserve her life. This narrative of Widow Zarephath's problematic response has rarely been researched and discussed in detail. This research centers on two main elements of this narrative, namely first, the widow Sarfat's response who made the decision to believe Elijah's words as God's prophet and her obedience in carrying out Elijah's orders even though they were contrary to reality; second, Elijah's obedience in following God's orders. For this reason, this research was conducted in a descriptive qualitative manner, with the sub-genre of narrative literary analysis based on Richard Pratt's method, then this research found that the right decision of this widow has changed her life from crisis and disaster to the guarantee of her life maintenance with her son. The narrative story of the widow Zarephath should be an inspiration and reference for many believers, who are struggling with various life challenges. The right decision and choice can change the situation and condition of life.